Perbandingan Metode Multi Analysis Surface Wave dan Metode HVSR dengan Mengidentifikasi Karakteristik Bawah Permukaan Jaringan Monitoring Gempabumi Wilayah Jawa Tengah - Yogi Widjayanti, Retno; Adhi, M. Aryono; Pramono, Sigit; Setyo Rahman, Aditya; Tawakal, Moh.Iqbal; Ardiansyah, Adam (Jurnal Pendidikan Matematika : Judika Education, 2025)
A region’s geological medium provides distinct local features that affect the propagation of seismic waves. This study looked at subsurface conditions down to 30 meters in order to assess the potential for seismic wave amplification during earthquakes. This research aims to determine the subsurface characteristics using the shear wave (Vs) parameters obtained using the multichannel analysis of surface waves (MASW) method.Twenty-four vertical geophones with a natural frequency of 4.5 Hz were subjected to the MASW technique. Through shear wave analysis, site classification was conducted referring to the Indonesian National Standard (SNI) 1726:2019, enabling evaluation of potential amplification across various sites. Reference sensors were selected from locations across Central Java, including the MBJI (Banjarnegara), KWJI (Wonosobo), KBJN and GTJI (Temanggung), GBJI (Batang), NSM01 (Central Semarang), SMRI and SMRIB (Tembalang), and BOJI (Boyolali).The lowest Vs30 value (165.1 m/s) was recorded at site NSM01 (Pendrikan Kidul, Central Semarang), while the highest (1868 m/s) was recorded at MBJI (Majalengka, Banjarnegara). Most reference sites were classified as Site Class C (very dense soil and soft rock). However, NSM01 was categorized as Site Class E (Soft Soil), indicating a higher potential for ground motion amplification, while MBJI presented minimal amplification risk due to its hard rock base.The findings highlight the importance of subsurface characterization for seismic hazard mitigation. The variation in Vs30 across the study sites reflects the lithological differences that directly affect the ground response during seismic events. Therefore, MASW provides essential data for improving earthquake-resistant infrastructure planning in Central Java.